Association between frailty syndrome and physical activity in patients with coronary artery disease and multivessel coronary artery disease - K. E. Krivoshapova; O. L. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To assess the relationship between frailty syndrome (FS) and physical activity (PA) in patients with multivessel coronary artery disease (CAD).Material and methods. The study included 387 patients with CAD. To identify prefrailty and FS, the authors used the questionnaire “Age is not a drawback”, and the “Mini-Cog” screening test. The analysis of PA was carried out using the Global physical activity questionnaire (GPAQ). Statistical processing was carried out using the IBM SPSS Statistics 26.0.0 software. The differences were considered significant at p≤0,050.Results. The prevalence of FS among CAD patients was 47% (n=181), whereas the prevalence of prefrailty was three times lower — 15% (n=58). The majority of patients with prefrailty and FS (32 (55,2%) and 93 (51,4%), respectively) had low PA levels, while patients with moderate PA levels were not likely to have FS (n=80 (54,1%)). Middle-aged women without FS were significantly more likely to belong to the moderate PA group (p=0,036). The multivariate analysis proved that the PA level is associated with the manifestation of frailty in patients with multivessel CAD.Conclusion. Manifestation of FS in patients with multivessel CAD is associated with low PA level.